The International Encyclopedia of Gender, Media, and Communication 2020
DOI: 10.1002/9781119429128.iegmc009
|View full text |Cite
|
Sign up to set email alerts
|

Doxxing

Abstract: Doxxing (or doxing) is a complex, gendered form of online harassment that breaches perceived privacy boundaries by releasing information through online mass media channels, resulting in physical and online consequences for a target. Doxxing often occurs in conjunction with other forms of online abuse and entangles online and physical environments in complicated and gendered ways that differ on a case‐by‐case basis. While both women and men experience doxxing, women are more likely to receive greater amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Based on their study, the authors concluded that given the internet's decentralised nature, it is difficult (if not impossible) to control the effects of this practice (ibid.). Online public shaming operates autonomously under decentralised and dispersed principles that make it deeply problematic since it is not possible to control the outcome (therefore, it is usually disproportionated); it tends to disrespect people's privacy (as it involves personal information), and thus it may easily become doxing since personal information can be used to harass, intimidate or blackmail the targets (Billingham and Parr, 2020;Eckert and Metzger-Riftkin, 2020).…”
Section: Online Public Shaming: the Moral Dilemmas Of An Extended Pra...mentioning
confidence: 99%
“…Based on their study, the authors concluded that given the internet's decentralised nature, it is difficult (if not impossible) to control the effects of this practice (ibid.). Online public shaming operates autonomously under decentralised and dispersed principles that make it deeply problematic since it is not possible to control the outcome (therefore, it is usually disproportionated); it tends to disrespect people's privacy (as it involves personal information), and thus it may easily become doxing since personal information can be used to harass, intimidate or blackmail the targets (Billingham and Parr, 2020;Eckert and Metzger-Riftkin, 2020).…”
Section: Online Public Shaming: the Moral Dilemmas Of An Extended Pra...mentioning
confidence: 99%
“…Doxing refers to the public exposure of private documents and information without consent and with the intent to humiliate, harass, intimidate, punish and/or blackmail targets, or condemn certain actions and ideas (Carty & Reynoso Barron, 2019; Eveleth, 2015; Fish & Follis, 2016; Eckert & Metzger-Riftkin, 2020). Trottier (2017) categorizes doxing along several axes, including: doxer, target, and/or law enforcement.…”
Section: Contentious Politics Of Data and Data Activismmentioning
confidence: 99%
“…Doxxing is the act of publicly publishing personal or private information about an individual on the Internet, often with malicious intent[24].…”
mentioning
confidence: 99%